Exploring the Impact of the “RUEU?” Game on Greek Students’ Perceptions of and Attitudes to European Identity - Jimoyiannis, Athanassios; Boyle, Elizabeth A.; Tsiotakis, Panagiotis; Terras, Melody M.; Leith, Murray S. (Frontiers in Psychology, 2022)
European identity is a complex, multi-faced and inherently imprecise concept relating to a range of socio-political and psychological factors. Addressing this topic in educational practice, particularly with respect to Higher Education students, constitutes a complex and open problem for research. This paper reports on an experimental study designed to explore the effectiveness of the educational game “RUEU?” in supporting university students in understanding the key socio-political issues regarding European identity. Quantitative data regarding Greek university students’ (N=92) attitudes to European identity, before and after playing the game, were collected. Students’ performance of the game group (N=46) was compared with that of a control group (N=46) who explored the same issues about European identity through a tutor-guided discussion. The findings showed that both instructional interventions were effective but in different ways. The participants in the game-based group appeared more attached to the EU after the intervention and moved towards a more balanced description of their Greek and European identity. On the other hand, the students in the control group rated higher what ‘European identity’ and being EU citizen means to them. The findings indicated the potential of game-based interventions to deliver not only academic content but also to promote students’ reflection and influence them at an attitudinal and emotional level.